GAMBARAN PENGETAHUAN IBU HAMIL TENTANG MANFAAT IMUNISASI TETANUS TOXSOID DI DESA TAMBUSAI TENGAH WILAYAH KERJA PUSKESMAS TAMBUSAI KABUPATEN ROKAN HULU TAHUN 2012 - WAHYUNY, ROMY; PURNAMASARI, IDA (Jurnal Martenity and Neonatal, 2012)
Provision of tetanus toxoid immunization (TT) is granting immunity to tetanus penyaki to pregnant women and their fetuses. The process of entry into the bodys immunity covers had suffered from the disease, allowing the body to form immunity against the disease. Based Test Analysis report in Indonesia in 2005 - 2006 prepared by WHO in collaboration with the Ministry of Health, tetanus remains a major cause of mortality and maternal and neonatal morbidity. Deaths from tetanus in developing countries 135 times higher than in developed countries. Objective knowledge is knowing pregnant women about the benefits of immunization Tetanus Toxoid (TT) in the village of Middle Tambusai Tambusai Work Area Health Center